OBJECTIVES OF USING KYRGYZ PROVERBS IN KYRGYZ LANGUAGE LESSONS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to issues related to the nature, characteristics, and objectives of using Kyrgyz proverbs in Kyrgyz language lessons in accordance with modern requirements, which include the importance of considering proverbs as part of the Kyrgyz language lesson content. Additionally, proverbs are examined as expressive illustrative tools that represent complete artistic texts in terms of content
Keywords: Kyrgyz proverb, Kyrgyz language lesson, requirements for teaching Kyrgyz language, lesson content, objectives of using proverbs in lessons, expressive teaching tools, literary text, scientific information